UNCERTAINTY, MONEY AND THE “FAIR” RATE OF INTEREST - Chytil, Zdenek; Maslo, Lukas (European Scientific Journal, ESJ, 2015)
This paper presents a redefinition of notion of the inter-temporal distributional neutrality underlying the “fair” rate of interest of Lavoie (1999). The authors re-define the notion by replacement of the labor-time constant purchasing power method by a more feasible method of a discounted value of consumption. Next, a general proof is provided by the authors of Lavoie’s postulate of the equality of the real “fair” rate of interest to the productivity growth rate. This proof is provided separately for a nonproductive and a productive economy. Subsequently, the authors present their own 45° “fair” rate model which inter-relates both the real and nominal “fair” rates with the productivity growth rate in a single graphical scheme. Finally, the authors amend their own center-equilibrium underemployment model by this 45° “fair” rate model to produce a complex fair-rate-amended center-equilibrium underemployment model. This model incorporates Lavoie’s “fair” rate of interest into a fundamental-uncertainty-based model of underemployment with an endogenous money supply.